Towards Sustainable High‐Performance Thermoplastics: Synthesis, Characterization, and Enzymatic Hydrolysis of Bisguaiacol‐Based Polyesters - Curia, Silvio; Biundo, Antonino; Fischer, Isabel; Braunschmid, Verena; Gübitz, Georg M.; Stanzione, Joseph F. (ChemSusChem, 2018)
The utilization of wood‐derived building blocks (xylochemicals) to replace fossil‐based precursors is an attractive research subject of modern polymer science. Here, we demonstrate that bisguaiacol (BG), a lignin‐derived bisphenol analogue, can be used to prepare biobased polyesters with remarkable thermal properties. BG was treated with different activated diacids to investigate the effect of co‐monomer structures on the physical properties of the products. Namely, derivatives of adipic acid, succinic acid, and 2,5‐furandicarboxylic acid were used. Moreover, a terephthalic acid derivative was used for comparison purposes. The products were characterized by 1H NMR spectroscopy, attenuated total reflectance FTIR spectroscopy, gel‐permeation chromatography, thermogravimetric analysis, and differential scanning calorimetry to assess their structural and thermal properties in detail. The polymers showed glass‐transition temperatures ranging up to 160 °C and thermal stabilities in excess of 300 °C. Furthermore, the susceptibility of the polyester to enzymatic hydrolysis was investigated to assess the potential for further surface functionalization and/or recycling and biodegradation. Indeed, hydrolysis with two different enzymes from the bacteria Thermobifida cellulosilytica led to the release of monomers, as quantified by HPLC. The results of this study indicate that our new polyesters represent promising renewable and biodegradable alternatives to petroleum‐based polyesters currently employed in the plastics industry, specifically for applications in which high‐temperature stability is essential to ensure overall system integrity. Think BG: Bisguaiacol (BG), a lignin‐derived bisphenol analogue, is treated with different activated diacids to investigate the effect of the co‐monomer structures on the physical properties of the products. The polymers show glass‐transition temperatures ranging up to 160 °C and thermal stabilities in excess of 300 °C. These new polyesters hold promise for use as renewable and biodegradable alternatives to petroleum‐based polyesters.